PARTISISPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH DI KABUPATEN POHUWATO - Muslimah Muslimah (AkMen JURNAL ILMIAH, 2011)
Public participation in the formation of local regulation is critical in determining the success of the development process in inonesia. Because community participation is a prerequisite in determining the success of the development process in Indonesia The successful implementation of development is inseparable from the active participation of community members in a region or city, either as part of the social system as well as the individual who is a very important part of the system of regional governance, because in principle the implementation of development in the area proposed to build a prosperous society and spiritual material in the area. The successful implementation of the development is inseparable from the active participation of community members in a region or city, either as part of the social system as well as the individual who is a very important part of the system of local government, because in principle the implementation of development in the area proposed to build a prosperous society and material spiritual in that area.